Życie codzienne – między racjonalnością działań a autorytetem. Na przykładzie diagnozy społecznej Ericha Fromma - Paszenda, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In accordance with the sociological concept of the world by Alfred Schütz, the world of everyday life constitutes the object of activities and interactions of given individuals, that – in turn – have to gain control over it, but also modify it in order to accomplish own goals, within the framework of such world, and amongst others. In such context, it comes across as particularly interesting to recognize whether a contemporary man acts accordingly to own needs, desires and goals, and what role in own activities is played by the authority. In this article the attempt to answer these questions is made by the author on the basis of the social diagnosis carried out by an American psychologist and sociologist – Erich Fromm.
Keywords: autorytet; Erich Fromm; pedagogika codzienności; racjonalność; życie codzienne